2000
DOI: 10.1097/00000658-200004000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-10 But Not Interleukin-6 Is Related to Clinical Outcome in Patients With Resectable Hepatocellular Carcinoma

Abstract: In patients with HCC, the preoperative serum IL-10 level is related to the clinical outcome. IL-10 may play an important role in the progression of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
2
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 33 publications
7
96
2
1
Order By: Relevance
“…Our results echo a previous study indicating that the serum IL-10 level was an adverse prognostic factor for patients with HCC after surgical resection. 18 With respect to inoperable HCC, to our knowledge, there has only been 1 retrospective series based on 74 patients; in that series, it was demonstrated that a serum IL-10 level >10 pg/mL (ie, log IL-10 level >1 pg/mL) was a negative prognostic factor. 23 However, in that study, the independent prognostic significance of IL-10 was not determined by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results echo a previous study indicating that the serum IL-10 level was an adverse prognostic factor for patients with HCC after surgical resection. 18 With respect to inoperable HCC, to our knowledge, there has only been 1 retrospective series based on 74 patients; in that series, it was demonstrated that a serum IL-10 level >10 pg/mL (ie, log IL-10 level >1 pg/mL) was a negative prognostic factor. 23 However, in that study, the independent prognostic significance of IL-10 was not determined by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-infl ammatory characteristics of IL-10 downregulate the host immune response [25]. A high IL-10 level was suggested to contribute to a relative state of immunosuppression in patients with hepatocellular carcinoma [26]. Matsuguchi et al [27] reported that high serum IL-10 levels in patients with hepatocellular carcinoma presumably also resulted from the secretion of IL-10 by tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, T-cell suppression derived from tumor-secreted IL-10 becomes one of the major barriers to T-cell immunotherapy of tumors. Clinically, the detectible serum IL-10 in cancer patients becomes a negative indicator for clinical outcome 17,18 TNF-a is a multifunctional cytokine with a broad spectrum of activities. It activates IL-2R/IFN-g expression and cytotoxicity of T cells, 19 and stimulates T-cell proliferation and activation 20 through activation of nuclear factor-kappa B (NF-kB) involving multiple cytokine activation.…”
Section: Introductionmentioning
confidence: 99%